Electropolymerization of 5-Indolylboronic Acid: Morphological, Spectroscopic, and Electrochemical Characterization with Perspective Toward Functional Applications - Aguirre-Quintana, M; Aguirre-Quintana, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Poly(5-indolylboronic acid) was synthesized electrochemically via cyclic voltammetry using various electrodes, including screen-printed carbon electrodes, glassy carbon electrodes, highly oriented pyrolytic graphite, and 304 stainless steel. This study provides a thorough analysis of the resulting conducting polymer’s electrochemical behavior, morphological and structural characteristics, and potential applications. The following techniques were employed: cyclic voltammetry, electrochemical impedance spectroscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, and field-emission scanning electron microscopy. The polymer exhibits pH-dependent redox activity within the pH range of 4–10, displaying Nernstian behavior and achieving a specific areal capacitance of 0.234 mF∙cm−2 on an SPCE electrode. This result highlights the electrode’s efficiency in terms of charge storage. Impedance data indicate that the modified electrodes demonstrate a substantial decrease in charge transfer resistance and improved interfacial conductivity compared to bare electrodes. Contact angle measurements show that the presence of boronic acid groups makes the polymer hydrophilic. However, when 5PIBA was incubated in the presence of molecules containing hydroxyl groups or certain proteins, such as casein, no adsorption was observed. This suggests limited interaction with functional groups such as amino, hydroxide, and carboxyl groups present in these molecules, indicating the potential application of the polymer in biocorrosion. 5PIBA forms homogeneous, stable, and electroactive coatings on various substrates, making it a promising and versatile material for electrochemical technologies, and paving the way for future functionalization strategies. © 2025 by the authors.